Echoes in the Walls - Andrews, V. C. (Virginia C.) (Thorndike, Maine : Center Point Large Print, 2021)
"Fern and her mother have lived as servants in Wyndemere House, the old Gothic mansion of the Davenport family, for as long as she can remember, and her friendship with Dr. Davenports son Ryder was never a problem . . . until they came of age. An intimate encounter following a high school prom brings the pair near-tragic consequences, and the forces of fate, arrogance, and class prejudice gather to crush their warm relationship. Still, the real threat to their happiness is something no one can control: the past, and the unspoken truths that lurk there. As cruel forces try to come between Fern and Ryder, what really holds the biggest threat to their happiness is the past, and the truths it threatens them with."--
Keywords: Teenagers -- Sexual behavior; Fiction; High school students -- Fiction; Household employees -- Fiction; Social conflict -- Fiction; Incest -- Fiction; Family secrets -- Fiction; Fiction; Gothic fiction